1993
DOI: 10.1002/pca.2800040205
|View full text |Cite
|
Sign up to set email alerts
|

The structure of velutinol A, an anti‐inflammatory compound with a novel pregnane skeleton

Abstract: The isolation and purification of velutinol A, a potent anti‐inflammatory agent from Mandevilla velutina is reported together with spectroscopic evidence which shows that the structure comprises a novel pregnane skeleton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The phytochemical studies of this plant have allowed the isolation and identification of velutinol A (1), a unique compound con-sisting of a 15,16-seco-14β,17α-pregn-5-ene core with cagelike framing in the D, E, and F rings, from M. velutina rhizomes in 1993 by Calixto and co-workers ( Figure 1). [5] Further pharmacological studies showed that 1 has potent anti-inflammatory activity and behaves as a selective antagonist for the B1R subtype. [6] To the best of our knowledge, 1 is the first and only B1R antagonist among nonpeptide natural products to be published to date.…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical studies of this plant have allowed the isolation and identification of velutinol A (1), a unique compound con-sisting of a 15,16-seco-14β,17α-pregn-5-ene core with cagelike framing in the D, E, and F rings, from M. velutina rhizomes in 1993 by Calixto and co-workers ( Figure 1). [5] Further pharmacological studies showed that 1 has potent anti-inflammatory activity and behaves as a selective antagonist for the B1R subtype. [6] To the best of our knowledge, 1 is the first and only B1R antagonist among nonpeptide natural products to be published to date.…”
Section: Introductionmentioning
confidence: 99%
“…The compound of interest was extracted from lyophilized cells with 2 volumes of ethyl acetate at 4ºC/7 days. The extract was filtered, concentrated under reduced pressure (crude extract), followed by the isolation of velutinol A by column chromatography on silica gel, using methylene chloride with increasing amounts of ethyl acetate as eluent (23). The presence of the compound in the column effluent was monitored by TLC on silica gel (Kilselgel 60 F 254 , 0.25 mm, Merck, Darmstadt, Germany), using hexane:diisopropyl ether:acetone (4:4:3) as the solvent system.…”
Section: Chromatographic Analysis Of Velutinol Amentioning
confidence: 99%
“…Illustrol and its derivatives isolated from Mandevilla illustris are instead 14,15-seco-21-nor-pregnane derivatives, characterized by the opening of ring D between C-14 and C-15 and by the occurrence of two ketal functions on C-14 and C-20 generating three five-membered rings but without a methyl group at C-20 [48][49][50]. 15,16-Secopregnanes isolated from Mandevilla velutina showed the opening of the ring D between C-15 and C-16 and the presence of one ketal function on C-16 and one hemiketalic function on C-15 generating one six-membered ring and two five-membered rings [45][46][47]. Another secopregnane-type skeleton more present in the family Asclepiadaceae and particularly in Cynanchum spp.…”
Section: Chemistrymentioning
confidence: 98%
“…[36][37][38][39][40][41][42][43] and Tylophora tanakae [44], and from Mandevilla spp. (Apocynaceae) [45][46][47][48][49][50][51]. From Cynanchum spp.…”
Section: Chemistrymentioning
confidence: 99%